Analysis of The Effect of Push Factors and Pull Factors on Tourists’ Revisit Intention To Pahawang Island, Pesawaran District, Lampung Province - Marmaiyatno; Himawan Brahmantyo; Sri Mariati (International Journal of Travel, Hospitality and Events, 2023)
Purpose: This study aims to analyze how the push and pull motivations and their influence on the desire of tourists to return to Pahawang Island. Research Methods: The research uses a quanlitative approach,The population of this study was tourists who came to Pahawang Island in the period 2019 with a sample of 100 respondents. Sampling used the Incidental Sampling technique. The questionnaire was tested for validation and reliability, as well as the classical assumption test to meet the requirements using Linear Regression as an analytical tool. Results and discussion: The results obtained in this study show that the motivation of both the push factor and pull factor have significant and positive influence on the interest in revisiting. Implication: Understanding how the push factors and pull factors on the intention to revisit can provide input for the tourism office and Tourism Destination Operator, especially on Pahawang Island, this research has theoretical and practical implications.             Keywords: Push Factors, Pull Factors, Revisit intention, Pahawang Island.